2020
DOI: 10.1177/0300060520953234
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hub genes in colon cancer via bioinformatics analysis

Abstract: Objectives This study aimed to investigate hub genes and their prognostic value in colon cancer via bioinformatics analysis. Methods Differentially expressed genes (DEGs) of expression profiles (GSE33113, GSE20916, and GSE37364) obtained from Gene Expression Omnibus (GEO) were identified using the GEO2R tool and Venn diagram software. Function and pathway enrichment analyses were performed, and a protein–protein interaction (PPI) network was constructed. Hub genes were verified based on The Cancer Genome Atlas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…A recent publication has also proposed the significant role of syntrophin beta 1-SNTB1 as prognostic marker for colon cancer metastasis (26). Moreover, it has been found that integrin betalike 1 -ITGBL1 is involved in the colon cancer development and metastasis (27) whileTACSTD2 and LEMD1 belong to the significant up-regulated genes of colon cancer (28,29). For the case of under-expressed MEGs found in our analysis, it has been indicated that the lower levels of PPARGC1A and SLC26A2 could increase colon cancer risk, proliferation and propagation and they have been proposed as possible candidate targets for cancer therapy (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication has also proposed the significant role of syntrophin beta 1-SNTB1 as prognostic marker for colon cancer metastasis (26). Moreover, it has been found that integrin betalike 1 -ITGBL1 is involved in the colon cancer development and metastasis (27) whileTACSTD2 and LEMD1 belong to the significant up-regulated genes of colon cancer (28,29). For the case of under-expressed MEGs found in our analysis, it has been indicated that the lower levels of PPARGC1A and SLC26A2 could increase colon cancer risk, proliferation and propagation and they have been proposed as possible candidate targets for cancer therapy (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, amplification was found as genetic alterations in 0.57% of the patients. In GBM, CCNB2 acted as a potential biomarker and played a vital role in Cellular Senescence and cell cycle [68]. These have missense mutation at location P80S having phosphorylation PTM site and amplification in 0.57% of the patients and shallow deletion copy number alterations.…”
Section: Discussionmentioning
confidence: 99%
“…CCNB2 also found to promote cell cycle progression resulting in tumorigenesis in case of triple negative breast cancer (Wu et al, 2021). It was also identified in the cell cycle progression leading to poor prognosis of HCC (Liu et al, 2020). In this study, amplification was found as genetic alterations in 0.57% of the patients.…”
Section: Discussionmentioning
confidence: 99%